Evaluation of unsaturated soil slope stability by incorporating soil-water characteristic curve - Zhai, Qian (2022)
Loess soils are unsaturated and widely distributed in the northwest zone in China. Many steep slope of unsaturated are observed are observed to be naturally stable. However, a low factor of safety (FoS) for these slopes would be computed from the slope stability analysis following local code practices. It seems that the analyzed results following the local code practices do not agree with the real condition as observed in the field. It is commonly known that soil suction plays an important role in slope stability due to a higher shear strength of the unsaturated soil as compared with that of the saturated soil. In this paper, it is observed that the computed FoS can also be affected by unsaturated unit weight of the soil. However, the effect of unsaturated unit weight of the soil on the slope stability is commonly ignored in engineering practice. Therefore, both the effects of shear strength and unit weight of the unsaturated soil on the computed FoS of unsaturated soil slope are investigated in this study. It is observed that the unsaturated unit weight of soil on the computed FoS increases with increase in slope angle. It is also observed that the effects of the unsaturated shear strength and unsaturated unit weight on the computed FoS are more significant than the effect of 3D analyses compared to the 2D analyses on the FoS.